2014
DOI: 10.1111/1468-4446.12035
|View full text |Cite
|
Sign up to set email alerts
|

Towards intensive parenting? Changes in the composition and determinants of mothers' and fathers' time with children 1992–2006

Abstract: Contemporary expectations of good parenting hold that focused, intensive parental attention is essential to children's development. Parental input is viewed as a key determinant in children's social, psychological and educational outcomes, with the early years particularly crucial. However, increased rates of maternal employment mean that more parents are juggling work and family commitments and have less non-work time available to devote to children. Yet studies find that parental childcare time has increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
151
3
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 46 publications
16
151
3
16
Order By: Relevance
“…Su diferenciación se establece, como se ha apuntado, por sus contenidos y formas significantes. Se trata de espacios coherentes con los ámbitos de implicación paterna actual tal como lo establece la literatura (Dermott, 2008;Barbeta-Viñas y Cano, 2017;Craig, et al, 2014). 1) el espacio del hogar y de las tareas instrumentales, que comprende un conjunto de significaciones vinculadas con la producción de la vida y la crianza de los hijos; 2) el espacio relacional, donde se condensan los aspectos expresivos y comunicativos del papel del padre.…”
Section: Análisis Y Resultados: Las Imágenes De Los Hijos Jóvenes En unclassified
See 1 more Smart Citation
“…Su diferenciación se establece, como se ha apuntado, por sus contenidos y formas significantes. Se trata de espacios coherentes con los ámbitos de implicación paterna actual tal como lo establece la literatura (Dermott, 2008;Barbeta-Viñas y Cano, 2017;Craig, et al, 2014). 1) el espacio del hogar y de las tareas instrumentales, que comprende un conjunto de significaciones vinculadas con la producción de la vida y la crianza de los hijos; 2) el espacio relacional, donde se condensan los aspectos expresivos y comunicativos del papel del padre.…”
Section: Análisis Y Resultados: Las Imágenes De Los Hijos Jóvenes En unclassified
“…En cuanto al ejercicio de la paternidad, algunos trabajos señalan cómo los padres con niveles formativos superiores serían más propicios a orientar su tiempo e intereses a la crianza de los hijos en relación a los padres con niveles inferiores de formación (Craig et al, 2014;Bianchi et al, 2006). Otros apuntan que la implicación paterna y los estilos de paternidad se muestran diversos entre grupos sociales con niveles socioeconómicos y educativos distintos (Marsiglio y Roy, 2012).…”
Section: Acercamiento Al Análisis De La Implicación Paternaunclassified
“…According to this ideology, "methods of appropriate child-rearing are construed as child-centered, expert-guided, emotionally absorbing, labor-intensive and financially expensive" [Hays, 1998]. The term "intensive parenting" is intensively used in the literature: the influential ideology also begins to spread across fathers [Shirani, Henwood, Coltart 2012;Craig, Powell, Smyth 2014].…”
Section: Doimentioning
confidence: 99%
“…In this article, 'market time' stands for time spent in market work, as in Hallberg and Klevmarken (2003). Among these studies, a few have focused on the implications for primary and secondary child care (Nock and Kingston 1988;Gutiérrez-Domènech 2010;Craig et al 2014;Bryant and Zick 1996). The available evidence is mixed.…”
Section: Huong Dinh and Maria Racioneromentioning
confidence: 99%
“…In Spain, Gutiérrez-Domènech (2010) found that working mothers and fathers reduce primary child care time more than secondary child care when they increase their own work time. In Australia, Craig et al (2014) found that full-time employed parents spend less time for both primary and secondary child care than non-employed parents. However, they found no evidence of significant differences in child care time between part-time and full-time employed parents.…”
Section: Huong Dinh and Maria Racioneromentioning
confidence: 99%